2012
DOI: 10.4161/jig.20125
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of changes in microvascular and microstructural patterns upon magnifying endoscopy predicted the presence of extranodal gastric MALToma

Abstract: Background and objectives:Gastric MaLToma is difficult to recognize upon endoscopy. The aim of this study is to evaluate the application of microstructural and microvascular patterns in recognizing gastric MaLToma on magnifying endoscopy. Method: all patients with diagnosis of gastric MaLToma upon histology were recruited. They received magnifying endoscopy to observe for changes in microstructural and microvascular patterns. For patients with h pylori, eradication therapy would be given. For those without, ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…[7][8][9] In the past, open or laparoscopic surgery was performed to remove SMT even without an accurate diagnosis before treatment. [10,11] Open surgery results in large surgical trauma, delayed postoperative recovery, and a certain percentage of operation-related complications. Better than open surgery, laparoscopic surgery for SMTs has quicker recovery, higher quality of life after operation and shorter hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] In the past, open or laparoscopic surgery was performed to remove SMT even without an accurate diagnosis before treatment. [10,11] Open surgery results in large surgical trauma, delayed postoperative recovery, and a certain percentage of operation-related complications. Better than open surgery, laparoscopic surgery for SMTs has quicker recovery, higher quality of life after operation and shorter hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…7 Recently, retrospective studies have shown the characteristics of gastric MALToma on ME. Chiu et al 8 reported abnormal spider-like vasculature and disappearance of gastric pits in nine patients with histological diagnoses of gastric MALToma, while Ono et al 9 reported that non-structural areas with abnormal vessels were observed in 11 patients before treatment. The use of ME may help the endoscopist to take targeted biopsies from the abnormal areas.…”
Section: Discussionmentioning
confidence: 99%
“…Reported post-treatment ME findings include recovery of gastric pits and resolution of abnormal vascular pattern. 8 It was demonstrated that the disappearance of non-structural areas with abnormal vessels was related to pathological remission. 10 There is no consensus on treatment for those who fail to respond to eradication therapy.…”
mentioning
confidence: 99%